The Duration of Prophylactic Antibiotic Use for Esophageal Cancer Patients with Postoperative Infection and Nutritional Status - Ning D; Zhou L; Shi G; Fu M (International Journal of General Medicine)
Dong Ning,1,* Lin Zhou,2,* Guidong Shi,1 Maoyong Fu1 1Department of Thoracic Surgery, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China; 2Department of Ultrasound, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dong Ning, Department of Thoracic Surgery, Affiliated Hospital of North Sichuan Medical College, No. 1, Maoyuan South Road, Shunqing District, Nanchong, Sichuan, 63000, People’s Republic of China, Email dongningcb@21cn.comObjective: To verify the hypothesis that “the prophylaxis use time of antibiotics after esophageal cancer (EC) surgery ≤ 24 hours is associated with a lower postoperative infection rate and improvement of nutritional indicators”, a retrospective cohort analysis was conducted to compare the infection incidence and differences in serum nutritional indicators among patients with different medication durations (< 24 hours, 24– 48 hours, > 48 hours), and to identify independent risk factors for postoperative infection.Methods: A retrospective analysis was conducted on the data of 566 patients who underwent EC surgery in Affiliated Hospital of North Sichuan Medical College from January 2020 to October 2022. Patients were divided into three groups based on the duration of postoperative antibiotic prophylaxis: Group A (< 24 hours), Group B (24– 48 hours), and Group C (> 48 hours). The differences in postoperative infection incidence and nutritional indicators [serum albumin (ALB), prealbumin (PA), hemoglobin (Hb) levels] among the three groups of patients were compared. Multivariate logistic regression analysis was performed to analyze the risk factors.Results: There existed a significant difference in the nutritional indicators among the patients in the three groups after surgery (P< 0.05). On day 10 after surgery, the ALB, PA, and Hb levels of patients in group A were much higher than those in group B and group C (P< 0.05). There was no significant difference in the levels of ALB, PA, and Hb between Group B and Group C (P> 0.05). The infected group had a much higher proportion of patients with age ≥ 65 years, moderate pulmonary ventilation impairment, intraoperative blood loss ≥ 200mL, postoperative respiratory support with a tube, hospitalization days ≥ 25 days, and malnutrition than the uninfected group (P< 0.05). Age, lung ventilation, hospitalization days, and preoperative malnutrition were all risk factors for postoperative infection in EC patients (P< 0.05).Conclusion: This study verified the hypothesis that “antibiotic use time ≤ 24 hours is associated with a lower infection rate trend and an increase in nutritional indicators”, but the causal relationship could not be established due to the retrospective design. Age, pulmonary ventilation function, length of hospital stay, and preoperative malnutrition were independent risk factors for postoperative infection, supporting the clinical formulation of individualized antibiotic regimens based on the association between medication duration and infection/nutrition.Keywords: esophageal cancer, preventive use of antibiotics, postoperative infection, nutritional status